2012
DOI: 10.1371/journal.pone.0047361
|View full text |Cite
|
Sign up to set email alerts
|

Fusion Toxin BLyS-Gelonin Inhibits Growth of Malignant Human B Cell Lines In Vitro and In Vivo

Abstract: B lymphocyte stimulator (BLyS) is a member of the TNF superfamily of cytokines. The biological activity of BLyS is mediated by three cell surface receptors: BR3/BAFF-R, TACI and BCMA. The expression of these receptors is highly restricted to B cells, both normal and malignant. A BLyS-gelonin fusion toxin (BLyS-gel) was generated consisting of the recombinant plant-derived toxin gelonin fused to the N-terminus of BLyS and tested against a large and diverse panel of B-NHL cell lines. Interestingly, B-NHL subtype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Both GSK2830371 and bortezomib target the p38 MAPK signaling pathway [ 33 35 ], and activation of p38 MAPK has been found to cause MCL cell death [ 35 ]. As shown in Supplementary Figure S5 , GSK2830371 and bortezomib synergistically increased levels of phosphorylated p38 MAPK in a p53-independent manner.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both GSK2830371 and bortezomib target the p38 MAPK signaling pathway [ 33 35 ], and activation of p38 MAPK has been found to cause MCL cell death [ 35 ]. As shown in Supplementary Figure S5 , GSK2830371 and bortezomib synergistically increased levels of phosphorylated p38 MAPK in a p53-independent manner.…”
Section: Resultsmentioning
confidence: 99%
“…Most PPM1D substrates either initiate or contribute to cellular stress signals and the removal of activating phosphorylation has been thought to liberate cells from cellular stress [ 39 ]. p38 MAPK is generally a pro-apoptotic and stress-related protein that is regulated by PPM1D and the proteasome [ 33 35 ] and its activation has been found to cause MCL cell death [ 35 ]. Our data, which indicate that the pharmacologic inhibition of p38 significantly reduced GSK2830371/bortezomib lethality in both p53 wild-type and mutated MCL cells, suggest that this stress pathway contributes functionally to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Luster et al [ 25 ] have reported that treatment with rGel-BLyS, rGel fused to a B-lymphocyte stimulator, rapidly reduced the tumor burden and markedly prolonged survival in xenograft mouse models of spread lymphoma or leukemia; in this setting, cell death was not induced by caspase activation but rather was partially mediated by the ribotoxic stress response. Furthermore, the rGel-BLyS fusion toxin combined with the proteasome inhibitor bortezomib restrained lymphoma growth and down-regulated nuclear factor kappa B (NF-κB) activity, which is critical for cellular proliferation and survival [ 26 ].…”
Section: Anti-tumor Activitymentioning
confidence: 99%
“…Dose–response curves of BLyS-Gel with and without latrunculin A pretreatment were superimposable and therefore suggested that internalization did not involve an actin-cytoskeleton-dependent endocytic mechanism. Nonetheless, Luster et al reported that BLyS-Gel was localized to lysosomes after internalization [ 165 ]. They showed that when cells were treated with chloroquine, a drug that accumulates in acidic endosomes/lysosomes, leading to their rupture, the fusion toxins were more efficacious.…”
Section: Target Antigens For Approved Adcs and Their Endocytosis Characteristicsmentioning
confidence: 99%